Does living in a community with more educated mothers enhance children's school attendance? Evidence from Sierra Leone. (January 2016) - Kamanda, Mamusu; Madise, Nyovani; Schnepf, Sylke
Highlights: Mothers' education within a community increases secondary school attendance. Mothers' education in a household increases primary school attendance. Household poverty reduces attendance more at secondary school than at primary school. Primary school attendance is lower in poor rural than in poor urban communities. The difference in attendance between boys and girls is not significant. Abstract: In Sierra Leone girls are 23.4% less likely to attend secondary education than boys. This difference between sexes increases the gender gap in educational attainment since women's education is positively associated with children's educational wellbeing. This paper investigates the relationship between children's school attendance, their mothers' level of education, as well as the overall level of women's education at the community level in Sierra Leone using multilevel statistical modelling techniques and the country's 2008 Demographic and Health Survey data. The findings suggest that, regardless of a child's own mother's education, an increase in the proportion of mothers with secondary or higher education in a community by 10% improves the probability of attending junior secondary school significantly by 8%; a 50% increase improves the likelihood of attending school by 45%. There was no significant relationship between the proportion of better educated mothers in a community and primary school attendance. However, relative to children whose mothers had no formal education, children whose mothers had attained primary, secondary or higher education were 7%, 14% and 22% more likely to attend primary school respectively. Future policies should seek to promote girls' education at post-primary education and develop community based programmes to enable the diffusion and transmission of educational messages.